FeLIX is a restriction factor for mammalian retrovirus infection - Pramono, Didik; Takeuchi, Dai; Katsuki, Masato; AbuEed, Loai; Abdillah, Dimas; Kimura, Tohru; Kawasaki, Junna; Miyake, Ariko; Nishigaki, Kazuo (Journal of virology, 2024)
Retroviruses are unique in using reverse transcriptase to convert RNA genomes into DNA, infecting germ cells, and transmitting to offspring. Numerous ancient retroviral sequences are known as endogenous retroviruses (ERVs). The soluble Env protein derived from ERVs functions as a co-factor that assists in FeLV-T infection. However, herein, we show that the soluble Env protein exhibits antiviral activity and provides resistance to mammalian retrovirus infection through competitive receptor binding. In particular, this finding may explain why FeLV-B transmission is not observed among domestic cats. ERV-derived molecules can benefit animals in an evolutionary arms race, highlighting the double-edged-sword nature of ERVs.